Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.25301/jpda.261.26
|View full text |Cite
|
Sign up to set email alerts
|

A Study of 89 Cases of Oral Squamous Cell Carcinoma Presenting at Teaching Hospitals of Lahore, Pakistan

Abstract: ABSTRACT:OBJECTIVE: Oral squamous cell carcinoma (OSCC) is one of the most prevalent malignant neoplasm in south Asia and a major public health problem in Pakistan due to its high morbidity and poor survival rates. The objective of the study was to describe the clinical pattern of oral squamous cell carcinoma in tertiary care hospitals of Lahore. METHODOLOGY:A cross sectional study was done at tertiary care hospitals of Lahore where demographic and clinical data of eighty nine histologically diagnosed cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…This increase in the incidence of OSCC of buccal mucosa preferably in our part of the world is due to habit of keeping betel nut and gutka in the buccal pouch for longer duration of time which significantly produce a sense of well-being and increased capacity to work by stimulation of parasympathetic nervous system 21 and increases the accumulation of carcinogenic substance into the involved area. 3,22 In contrary to this, international literature shows tongue as the most commonly involved site followed by floor of the mouth attributed to increase exposure of carcinogenic substances through smoking. 23,24 This finding is also consistent with the study conducted by Syamet al 25 Ebrahimiet al 26 have reported that T stage and N stage were important factors affecting regional recurrence in OSCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in the incidence of OSCC of buccal mucosa preferably in our part of the world is due to habit of keeping betel nut and gutka in the buccal pouch for longer duration of time which significantly produce a sense of well-being and increased capacity to work by stimulation of parasympathetic nervous system 21 and increases the accumulation of carcinogenic substance into the involved area. 3,22 In contrary to this, international literature shows tongue as the most commonly involved site followed by floor of the mouth attributed to increase exposure of carcinogenic substances through smoking. 23,24 This finding is also consistent with the study conducted by Syamet al 25 Ebrahimiet al 26 have reported that T stage and N stage were important factors affecting regional recurrence in OSCC.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 In Pakistan, Oral SCC is considered as the second most common cancer diagnosed in both male and female, constituting 15% of estimated new cases compared to 3% found worldwide. 3 In developing countries, the prevalence of intraoral cancer appears to be rising, especially in men due to habit of eating tobacco, betel quid and areca nut. 4 These ingredients along with other factors such as alcohol consumption, low socioeconomic status, poor hygiene, poor diet, and viral infections, chronic irritation from ill-fitting dentures, rough, or fractured teeth.…”
Section: Introductionmentioning
confidence: 99%
“…4 In Pakistan Oral squamous cell carcinoma is a major public health problem due to its poor survival rates and high morbidity. 5 The most common sites of the oral cavity involved by SCC are tongue and floor of the mouth. There is an increased incidence of occult cervical metastasis in lesions involving floor of the mouth and tongue, even in earlier stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is the widest spread cancer of the oral cavity representing 90% of all the oral malignancies 1 . It is the sixth most common cancer worldwide and ranked the second highest in the Indian subcontinent including Pakistan 2 . Multiple factors contribute to the initiation and growth of OSCC in the oral epithelial cells such as smoked or smokeless tobacco, alcohol, infective agents, deficiency of nutrients, oral factors, and genetics 3,4 .…”
Section: Introductionmentioning
confidence: 99%